Analysis of Obstacles in Problem-Based Learning on the Development of Students Critical Thinking Skills at SMA Negeri 7 Bone - Nuraeni Mansur; Supriadi Torro; A. Octamaya Tenri Awaru; Najamuddin Najamuddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study examines the obstacles in implementing the Problem Based Learning (PBL) model to improve students’ critical thinking skills at SMA Negeri 7 Bone. The main challenges identified are limited learning resources, low student literacy, and high levels of student demotivation. Data were collected through interviews with teachers and analyzed using qualitative methods. The findings reveal that insufficient textbooks, weak internet access, and a lack of digital media hinder students' independent exploration and active participation. Low literacy skills reduce students' ability to analyze and understand information, while demotivation limits their engagement in learning activities. These factors collectively obstruct the development of critical thinking as intended by the PBL model. Addressing these issues requires a holistic approach involving improved learning resources, literacy programs, and motivational support to create an effective and active learning environment.